Effects of sociodemographic changes on the labour market of Galicia in Spain - Sánchez-Sellero, María Carmen; Sánchez-Sellero, Pedro; Martínez-Filgueira, Xosé Manuel (Wydawnictwo Uniwersytetu Ekonomicznego we Wrocławiu, 2017)
Recently, important societal changes have affected the labour market: declining birth rates, aging population, the delayed independence of young people, an increase in the number of households, new household structures (increases in small households and single-parent households), and an increase in female workers. As a consequence, any model of the Galician labour market should include the following explanatory variables: gender, marital status, household size, age, and education level. Using binary logistic regression, we analyze the effect of each variable on probability of job activity in several years (2003, 2007 and 2013); in Galicia (the northwest region of Spain). We show that the probability of job activity increases especially in women during the economic crisis (2013). In addition, men decide to reduce their retirement age during economic growth, whereas they prolong their retirement age during economic crises. Hence sociodemographic changes and economic cycle affect the probability of job activity
Argumenta Oeconomica, 2017, Nr 1 (38), s. 41-62
Keywords: labour market; demographic change; gender; activity; logit